2000
DOI: 10.1038/sj.onc.1203278
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor alpha and mouse models of human breast cancer

Abstract: Transforming growth factor alpha (TGFa) is a principal molecule in the normal and neoplastic development of the mammary gland. Binding of TGFa to the epidermal growth factor receptor (EGFR), activates the EGFRs' endogenous tyrosine kinase activity and stimulates growth of the epithelium in the virgin and pregnant mouse mammary gland. TGFa expression can be detected in breast cancer cells in vivo and in vitro and overexpression can elicit partial transformation or immortalized human and rodent mammary epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…The relationship between mammary development and tumorigenesis is highlighted by the observation that these mice also displayed signi®cant delays in mammary gland involution (Sandgren et al, 1995). As these mice still required multiple pregnancies for tumors to form, it is possible that this delay in involution may act to provide an expanded population of proliferating epithelial cells predisposed to transformation (Humphreys and Hennighausen, 2000). However, the long latency observed once again indicates that additional genetic events are necessary for tumor progression in this model.…”
Section: Egfr Ligandsmentioning
confidence: 85%
See 1 more Smart Citation
“…The relationship between mammary development and tumorigenesis is highlighted by the observation that these mice also displayed signi®cant delays in mammary gland involution (Sandgren et al, 1995). As these mice still required multiple pregnancies for tumors to form, it is possible that this delay in involution may act to provide an expanded population of proliferating epithelial cells predisposed to transformation (Humphreys and Hennighausen, 2000). However, the long latency observed once again indicates that additional genetic events are necessary for tumor progression in this model.…”
Section: Egfr Ligandsmentioning
confidence: 85%
“…TGF-a possesses strong homology to EGF and like EGF acts as a ligand for the EGFR. TGF and EGFR expression has been found to coincide with normal mammary epithelial proliferation in vivo (reviewed in Humphreys and Hennighausen, 2000). Early studies with transgenic mice expressing TGF-a weakly in the mammary gland showed increased cellular proliferation and fat pad developmental defects (Sandgren et al, 1990).…”
Section: Egfr Ligandsmentioning
confidence: 99%
“…Recent findings revealing distinctive molecular profiles for ERÀ tumors containing ErbB1 versus ErbB2 (Creighton et al, 2006) may shed light on these differences. Cystic papillary tumors in NRL-TGFa mice resemble those of other TGFa transgenic mice (Humphreys and Hennighausen, 2000;Rose-Hellekant and Sandgren, 2000;Arendt et al, 2006). Concurrent expression of heterozygous p53 results in aggressive solid tumors of varying types reflecting the tumor spectrum of p53 þ /À BALB/c mice (Blackburn et al, 2003;Jerry et al, 2000;Kuperwasser et al, 2000), although relative proportions cannot be determined due to low numbers of p53 þ /À mice in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…While TGFa-induced mammary tumorigenesis has been described using the WAP, MMTV and MT promoters (Humphreys and Hennighausen, 2000;Rose-Hellekant and Sandgren, 2000), estrogen sensitivity and/or the expression pattern of these traditional promoters has limited their application. MMTV-transgene expression is uniform at 6 weeks, but becomes focally expressed by 15 weeks (Gunther et al, 2002), and progesterone activates this promoter (Otten et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Next we compared the protein level of BDP1 in breast tumors from transgenic mice expressing HER2 or other oncogenes under the control of gene promoters, which restrict oncogene expression to the mammary alveolar epithelium (41)(42)(43)(44)(45). Although BDP1 was readily detected in all samples tested, its expression was maximal in the HER2-overexpressing tumor (Fig.…”
Section: Expression Profile Of Bdp1 Her2 and Egfr In Breastmentioning
confidence: 99%